2007
DOI: 10.1530/rep-06-0292
|View full text |Cite
|
Sign up to set email alerts
|

A molecular analysis of the population of mRNA in bovine spermatozoa

Abstract: Spermiogenesis represents the transition from haploid spermatids to spermatozoa. This process entails an extreme condensation of the nucleus and a loss of nearly all cytoplasmic content. The presence of messenger RNAs in the spermatozoa has previously been shown. Generally, these transcripts are considered to be remnants of spermiogenesis. However, it has recently been proposed that there may exist a function for these sperm-associated RNAs. To address the possibility of a functional role for these transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 40 publications
4
83
1
Order By: Relevance
“…Moreover, a very high abundance of sperm adhesins and most CRISP and Fn-type II mRNAs were found in ejaculated sperm, most of which exhibited weak or no expression in the testes (Song et al 2010(Song et al , 2011. A comparative analysis of the transcripts between bovine spermatids and mature sperm also revealed that although 36.81% were common in both cell types, only 4.5% were specific to mature sperm (Gilbert et al 2007). These data question the hypothesis that the RNA in sperm is leftover from spermiogenesis and suggest that sperm RNAs have other origins.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, a very high abundance of sperm adhesins and most CRISP and Fn-type II mRNAs were found in ejaculated sperm, most of which exhibited weak or no expression in the testes (Song et al 2010(Song et al , 2011. A comparative analysis of the transcripts between bovine spermatids and mature sperm also revealed that although 36.81% were common in both cell types, only 4.5% were specific to mature sperm (Gilbert et al 2007). These data question the hypothesis that the RNA in sperm is leftover from spermiogenesis and suggest that sperm RNAs have other origins.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of coding RNAs in sperms of humans (Lambard et al 2004), pigs (Yang et al 2009), bovines (Gilbert et al 2007, Lalancette et al 2008, mice (Fang et al 2014) and stallions (Das et al 2013) is well established. Even though the functions of the majority of the sperm mRNAs remain enigmatic, it has been proposed that sperm mRNAs may play roles in the regulation of sperm morphology, motility and capacitation and that sperm transcriptional profiles might provide clinical markers for male fertility (Lambard et al 2004, Li et al 2007, Bansal et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jasko et al (1990a) and findings provided a better concept of the biological importance of sperm RNAs, allowing the identification of biomarkers of stallion fertility. The sperm transcriptome has been studied in humans (Ostermeier et al 2002), boars (Kempisty et al 2008;Yang et al 2009) and bulls (Gilbert et al 2007;Bissonnette et al 2009;Feugang et al 2010), and the utility of sperm RNA as a marker of infertility has been explored (Miller 2000;Steger 2001), whereby differences in transcript levels in spermatozoa with different motilities (Bissonnette et al 2009;Lambard et al 2004), as well as between normal and abnormal sperm samples (Platts et al 2007;Steger et al 2003), have been reported. Krawetz (2005) demonstrated that some of the sperm RNAs can be delivered to the oocyte during fertilisation.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 A previous study, aiming to determine the functional role of mRNA transcripts in bull spermatozoa, supports the result that sperm RNA profiling is suitable for molecular diagnosis of male gamete quality. 18 There are some studies researching the levels of different transcripts of mRNA encoding molecules containing nuclear condensation, capasity and sperm function of spermatozoa. 19,20 In these studies, it has been submitted that the quality of sperm can be related with its mRNA distribution.…”
Section: Discussionmentioning
confidence: 99%